Wide spread of OXA-48-producing Enterobacteriaceae in Algerian hospitals: A four years’ study - Nadjet Aggoune; Hassiba Tali Maamar; Farida Assaous; Badia Guettou; Rym Laliam; Nabila Benamrouche; Ali Zerouki; Malek Naim; Kheira Rahal (Journal of Infection in Developing Countries)
Introduction: The aim of this study was to investigate the presence of carbapenemase-producing Enterobacteriaceae (CPE) in Algerian hospitals and to characterize the molecular types of carbapenemases found.